Donatenow: a crowdsourcing-based mobile application with geolocation and content-based filtering algorithm / Siti Rahayu Abdul Aziz and Nur Aqilah Balkis Hafiz Abu Bakar - Abdul Aziz, Siti Rahayu; Hafiz Abu Bakar, Nur Aqilah Balkis (Faculty of Computer and Mathematical Sciences, 2023)
In the realm of contemporary philanthropy, the landscape of donation strategies has undergone a remarkable transformation. Donation-based crowdfunding, a strategy characterized by pooling contributions from numerous individuals, each providing modest sums, has emerged as a powerful tool to fuel projects. The objective of this study is to develop a mobile application called DonateNow, designed to establish a charitable crowdsourcing system. This innovative system integrates crowdsourcing, geolocation technology, and a content-filtering algorithm to enhance the efficacy of philanthropic endeavors. The goal is to empower individuals, especially donors, with the ability to discern appropriate donation items and their corresponding target locations and to minimize donation wastage, ensuring that each contribution finds its intended recipient. The developmental trajectory of DonateNow aligns with agile methodologies, ensuring a streamlined and efficient project management process. The application's construction is rooted in Android Studio, while Firestore serves as its robust database foundation. The profound significance of the DonateNow application lies in its potential to bring about a transformational impact. Donors are empowered to make informed decisions about their contributions, optimizing the impact of their generosity. Simultaneously, recipients stand to benefit from a streamlining of donations, ensuring they receive only what is truly essential to their circumstances. By mitigating the squandering of resources on unwanted items, DonateNow emerges as a beacon of effective and efficient philanthropy. As the digital realm converges with the realm of benevolence, DonateNow holds the promise of reshaping the donation landscape and catalyzing positive change for both donors and recipients.